Perspektif Peneliti Outsider Terhadap Perilaku Keagamaan Masyarakat Muslim (Kajian pada Pemikiran Frederick M. Denny) - Fahri Hidayat (Universitas Muhammadiyah Magelang, 2019)
This study examines the approach used by Frederick M. Denny who is an outsider researcher about the religious behavior of Muslim communities. The method used is the library method. Meanwhile, the primary source used as a data source is the writing of F. M. Denny's in Richard C. Martin's anthology book. This study found that the approach used by Frederick. M. Denny in understanding the religious behavior of Muslim societies is a sociological approach by distinguishing rituals in Islam into two, namely official and popular rituals. Through this approach, Denny concluded that outside of official worship, in Islam there were also additional rituals performed by Muslim communities. The difference is that these additional rituals are local and vary by region